Exploring the school dropout factors among indigenous students in Melaka / Sheera Nabila Singar and Azizan Zainuddin - Singar, Sheera Nabila; Zainuddin, Azizan (Universiti Teknologi MARA, Shah Alam, 2017)
The main objective of this study was to determine the most contributing factors that influence indigenous student’s dropout from school in Alor Gajah, Melaka. It is specifically focused on the Indigenou students who came from nine schools in Alor Gajah Melaka area. This study employed quantitative approach and the data was analysed using the multiple regressions test. Education is one of the important aspects in achieving the Vision 2020 so that no one will be left behind in the modern development. Hence, it is the responsibility of the authority agencies to provide equal opportunity for every one of her citizens. In this context, if the indigenous people still dropout and left behind, it will be the problems for Malaysia to achieve the status of the developed country. This study found that there is a significant relationship between level of income, parent’s education background, infrastructure and basic amenities influencing Indigenous students to drop out from school. Indeed, parent’s education background revealed to be the most dominant factor in influencing Indigenous students to drop out from school. However, the findings do not generalize to every Indigenous students in Malaysia and only applicable to Alor Gajah, Melaka area. Further research needs to be done to add the distances as the independent variables to see the relationship of Indigenous students drops out from school.